The Effectiveness Of Human Resource Management In Improving Employee Performance At PT. Nafac Mitra Utama - Muhammad Zidan; Majang Palupi (Cita Konsultindo Research Center, 2023)
This internship report discusses matters related to the effectiveness of human resource management (HRM) in improving employee performance at PT. Nafac Mitra Utama. This study utilizes the theory of strategic human resource management, which focuses on enhancing the effectiveness of HRM implementation in the company. PT. Nafac Mitra Utama is a company operating in the field of construction, particularly technical consulting. This research adopts a qualitative approach with a descriptive method through interviews and direct observations. The conclusion of this study is that PT. Nafac Mitra Utama has implemented several strategic human resource management practices, as evidenced by how the company manages its human resources to enhance effectiveness and employee performance. Some of the strategic human resource management efforts undertaken include providing regular training and development, implementing effective communication within the company, offering both financial and non-financial compensation to employees, promoting job advancements, enhancing employee commitment, improving performance monitoring and evaluation systems, establishing health and safety procedures, and creating a harmonious work environment.